A Biological Safety Cabinet Certification Program: Experiences in Southeast Asia. (September 2016) - Whistler, Toni; Kaewpan, Anek; Blacksell, Stuart D.
Biological safety cabinets (BSCs) are the primary means of containment used in laboratories worldwide for the safe handling of infectious microorganisms. They provide protection to the laboratory worker and the surrounding environment from pathogens. To ensure the correct functioning of BSCs, they need to be properly maintained beyond the daily care routines of the laboratory. This involves annual maintenance and certification by a qualified technician in accordance to the NSF/American National Standards Institute 49-2014 Biosafety Cabinetry: Design, Construction, Performance, and Field Certification. Service programs can be direct from the manufacturer or through third-party service companies, but in many instances, technicians are not accredited by international bodies, and these services are expensive. This means that a large number of BSCs may not be operating in a safe manner. In this article, we discuss our approach to addressing the lack of trained and qualified personnel in Thailand who can install, maintain, and certify BSCs in a cost-effective and practical manner. We initiated a program to create both local and regional capacity for repair, maintenance, and certification of BSCs and share our experiences with the reader.